2017
DOI: 10.1590/1807-1929/agriambi.v21n9p645-650
|View full text |Cite
|
Sign up to set email alerts
|

Stability of ‘mangaba’ pulp powder obtained by freeze drying

Abstract: A B S T R A C TThis work examined the stability of lyophilized 'mangaba' pulp powder, rolled and packaged in plastic containers, with and without vacuum during 90 days of storage under room temperature, with evaluation of the parameters every 15 days. Analyses of ascorbic acid concentration, pH, color and water activity were carried out. It was found that ascorbic acid remained in accordance with the standards specified for daily consumption according to the Brazilian legislation in all analyzed packages, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This behavior is similar to that observed by other authors for fruit powders during storage. Conegero et al (2017) observed increase in the water's activity, evaluating the stability of 'mangaba' (Hancornia speciosa Gomes) powder along the 90 days of storage. Santos et al (2016) stored 'umbu-cajá' (Spondias spp.)…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…This behavior is similar to that observed by other authors for fruit powders during storage. Conegero et al (2017) observed increase in the water's activity, evaluating the stability of 'mangaba' (Hancornia speciosa Gomes) powder along the 90 days of storage. Santos et al (2016) stored 'umbu-cajá' (Spondias spp.)…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 96%
“…There are several studies seeking to understand the stability of food products during their storage, such as Galdino et al (2016), studying the stability of cactus pear (Opuntia ficus-indica) powder, Conegero et al (2017), studying 'mangaba' (Hancornia speciosa Gomes) pulp powder, Rodrigues et al (2018) evaluating a byproduct of 'jabuticaba' (Plinia cauliflora) stored in microcapsules, and Sousa et al (2016) evaluating the stability of cashew (Anacardium occidentale L.) juice powder dehydrated in a spouted bed.…”
mentioning
confidence: 99%
“…Only one study describes no longer than the physicochemical characteristics of the mangaba sherbet [ 3 ]. Aware of the nutritional and cultural importance of mangaba was developed a freeze-dried mangaba pulp flour with incorporated maltodextrin, which maintained the physicochemical and sensory characteristics of the fruit for up to 90 days, making it possible and easier to use it in the development of food products after the harvest period [ 89 , 90 ]. Yamashita et al.…”
Section: Known Biotechnological Applications Of Hancornia S...mentioning
confidence: 99%